(untitled) (International Journal of Engineering and Computer Science, 2017)
Information security is always the area of concern for cloud users. The confidentiality of the Electronic Health Records (EHRs) is major issue when commercial cloud servers are used by hospital staff to store the patients’ medical records because it can be viewed by everyone. There are various issues and challenges toward achieving detailed data access control based on cryptography. To achieve fine grained and scalable data access control for medical records stored in cloud servers, we propose Attribute Based Encryption (ABE) techniques such as key policy attribute based encryption, role based encryption, etc. to encrypt each patient’s medical record file. For this we describe an approach which enables storage which is secure and patient’s health data with controlled sharing. We explore key-policy attribute based encryption to gain patient access control policy such that everyone can download the data, but only authorized user can view the medical records. A high degree of patient privacy is maintained using multiple cryptographic algorithms applied on the various types of data